Measurement of Flexion Angle of the Finger Joint during Cylinder Gripping Using a Three-Dimensional Bone Model Built by X-Ray Computed Tomography. (6th January 2019) - Shimawaki, Satoshi; Murai, Takuma; Nakabayashi, Masataka; Sugimoto, Hideharu
Abstract : Motion analysis of the thumb and the four fingers during human gripping of a cylindrical object is a prerequisite for designing motion mechanisms in electronic arm prostheses and robotic hands. Conventional measurement methods include the use of angle sensors or multiple video recording of markers. In the present study, we performed X-ray computed tomography (CT) imaging on fingers gripping cylinders of three different diameters (10, 60, and 120 mm) and constructed a bone model based on these CT images to directly measure the flexion angle of each finger joint. We then compared the results with the flexion angles of joints measured using other methods. The subjects comprised 10 Japanese men with no hand injuries or diseases. Our results showed that smaller cylinder diameters were associated with significant increases in the flexion angle of all the joints of the four fingers. When focusing on the distal interphalangeal joint (DIP), there was no significant difference between any of the fingers for each of the cylinders, except between the index and middle fingers for the 10 mm-diameter cylinder. When focusing on the 10 mm-diameter cylinder, the flexion angle of the proximal interphalangeal joint (PIP) of each finger was significantly larger than that of the DIP and metacarpophalangeal joint (MP). However, no such significant difference was noted for the 120 mm-diameter cylinder. The coupling ratio (CR), which is the ratio of the flexion angles of the DIP and PIP, was significantly smaller for the 10 mm-diameter cylinder than for the 60 mm-diameter cylinder. However, there were no significant differences in CR between any of the fingers. A comparison of our study results with those derived using other methods indicated quantitative consistency for the DIP and PIP. However, for the MP, we noted differences that may be explained by the difficulty in determining the longitudinal axis of the metacarpal using other methods.